2018
DOI: 10.1002/jcp.26531
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers for the occurrence of lung adenocarcinoma from TCGA data mining

Abstract: The development of lung cancer is a combination of multifactor, multistage, and multiple genetic alterations processes. DNA methylation is an important factor. Currently, the study on the genome-scale epigenetic modification for studying the pathogenesis of lung cancer is still lacking. Here, we aimed to identify the epigenetic modifications of lung cancer, thus to provide scientific basis for the personalized medicine, and research of classification screening for lung adenocarcinoma patients. The DNA methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…We downloaded clinical records, RNAseqV2 level 3 gene level data, and DNA methylation level 3 data for 11,908 cases across 34 cancer types from TCGA (http://xena.ucsc.edu/welcome-to-ucsc-xena/). Profiling data of the TCGA-retrieved cases were generated using the Illumina HiSeq 2000 RNA Sequencing and Illumina Infinium Human Methylation 450 platforms, as described by the TCGA network [16, 17]. Gene transcription estimates for each gene were presented as in RNA-Seq using the Expectation Maximization (RSEM) software.…”
Section: Methodsmentioning
confidence: 99%
“…We downloaded clinical records, RNAseqV2 level 3 gene level data, and DNA methylation level 3 data for 11,908 cases across 34 cancer types from TCGA (http://xena.ucsc.edu/welcome-to-ucsc-xena/). Profiling data of the TCGA-retrieved cases were generated using the Illumina HiSeq 2000 RNA Sequencing and Illumina Infinium Human Methylation 450 platforms, as described by the TCGA network [16, 17]. Gene transcription estimates for each gene were presented as in RNA-Seq using the Expectation Maximization (RSEM) software.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have investigated the association between the BEX family and lung cancer. A previous study reported that high expression levels of BEX2 and BEX4 were significantly associated with a favorable prognosis in patients with LUAD (21). Furthermore, overexpression of BEX4 may promote LUAD cell proliferation and growth in vitro (22).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used HCC data from The Cancer Genome Atlas (TCGA; Zhu, Zhu, Wu, & Hu, 2018) to explore the differential expression level as well as the methylation level of the C19MC in HCC, together with evaluating the significant correlation between them. We further assessed the correlation between C19MC expression and clinical features.…”
Section: Introductionmentioning
confidence: 99%